Teacher's Competences for Using Visual Response Methods in the Literary Education Communication Model - Šrot, Kristina (Revija za elementarno izobraževanje, 2019)
In the article we present the method of visual response to literary texts, using the example of a folk tale from a foreign civilization circle titled “The Story of Caiman”. In considering the perceptions of pupils in the 5th grade of elementary school, our goal is to examine teacher competences for developing the pupils’ ability to perceive, understand and evaluate literary texts and on this basis, to assess the justification of content integration (JCI) in the curriculum of university teacher education. This problem was observed within the framework of the interdisciplinary connection between literature and fine arts, since it is only possible to achieve optimal use of aesthetically designed text as a didactic tool for the externalization of the learner's dialogue with literary proverbs, thus checking to what extent teachers are trained in these methods (Visual Response Method) in the communication model of literary education.